2012
DOI: 10.3111/13696998.2012.708689
|View full text |Cite
|
Sign up to set email alerts
|

Patients rank toxicity against progression free survival in second-line treatment of advanced renal cell carcinoma

Abstract: This study provides information to physicians about patient priorities when reviewing and selecting RCC therapies with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 18 publications
4
46
1
Order By: Relevance
“…Indeed, it was considered 30–40 % more important than the method of administration and time to an SSE. Consistent with many studies conducted in cancer [16, 17, 25, 26], method of administration held only a modest association with medication choice. Oral administration was most positively associated with choice, while a 1-h IV infusion every 3 weeks was most negatively associated with choice.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Indeed, it was considered 30–40 % more important than the method of administration and time to an SSE. Consistent with many studies conducted in cancer [16, 17, 25, 26], method of administration held only a modest association with medication choice. Oral administration was most positively associated with choice, while a 1-h IV infusion every 3 weeks was most negatively associated with choice.…”
Section: Discussionsupporting
confidence: 78%
“…Although symptomatic events (pain, SSEs, etc.) have been extremely important to patients with solid tumors [16], most studies conducted in cancer have found patients value OS or progression-free survival as the most important attribute when considering treatment options [17, 2426]. It is possible that the differences between our findings and those of the literature could be a function of tumor type (CRPC vs. other tumors), geography (Japan vs. the West), or another aspect of the methods (e.g., a more restricted range of OS levels vs. a wider range of OS levels; older, late-stage patients vs. younger, earlier-stage patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two sets of observations suggest that if higher overall dose levels can be maintained, alternate scheduling may permit greater daily sunitinib exposure, which may help the individual patient derive greater benefit from sunitinib. Additionally, proliferation of endothelial cells is proportionate to the time off of systemic therapy [9], and unfavorable prognosis is linked to rate of tumor growth while off therapy, generating a hypothesis that shorter breaks are in the patient's best interest.…”
Section: Discussionmentioning
confidence: 99%
“…The results from these studies together led to the recommended phase II dose of 50 mg on discontinuous schedules. In a study by Wong et al, fatigue and diarrhea were the most troublesome toxicities for patients, and patients were willing to forego 4.4 months of PFS to ameliorate their symptoms from severe to mild-to-moderate [9]. Interestingly, with the standard 4-week treatment followed by a 2-week break, a cyclic scoring pattern is observed in patient-reported quality-of-life indicators; with improvement in mean scores after the 2-week treatment break [5].…”
Section: Introductionmentioning
confidence: 99%